SUFI POEM âJOHNNY CASH GOES TO HELLâ: THE UNIVERSAL OF MORALS - Taufiqurrohman, Taufiqurrohman (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2016)
his research is aimed at finding the theme of a unique Sufi poem expressed by Tiel Aisha Ansari entitled âJohnny Cash Goes to Hellâ. The analysis used is Riffaterreâs Semiotic theory. The theory uses two stages of signification. The first finds lexical meaning that is called Heuristic reading. It functions as the footstep for the next signification. The next one explores second meaning that is called Hermeneutic reading. This signification consists of four steps: Hypogram Actual, Hypogram Potential, Model and Matrix. The result of research says that this poem uses character Johnny Cash and St. Peter as the signified. The dialogue was used by Tiel to share Johnnyâs thought. Johnny, the icon for Sufis, was considerate with what people had suffered from. The Hypogram Potential says that a Sufi sacrifices his comfort just for making people who are trapped by wrongness can go back to expedience. The model makes the distribution of meanings to be two, namely morals and universalism. The morals, especially considerate, can be universal. It can go across religions. This can be proved from the using of inter-religion symbols in the poem. Thatâs why âthe universal of moralsâ is the theme can be got here.